IPAS Implementation in Elementary Schools: How Teachers Build Student Understanding - Mia Komariah; Mohamad Yasin As’ary; Citra Bahadur Hanum; Bunyamin Maftuh (research, training and philanthropy institution Natural Aceh, 2023)
Merging science (IPA) and social studies (IPS) subjects into science and learning (IPAS) in elementary schools is challenging for teachers. This study aims to determine how teachers build students' understanding of IPAS subjects. The research method used is descriptive qualitative through case studies. Data collection techniques using observation, in-depth interviews, and documentation studies. The research subjects were SDIT At-Taqwa KPAD Bandung IV teachers. Data analysis utilizes Miles and Huberman's techniques. Based on the research results, the teacher's way of building student understanding is by highlighting the dominant material between Science and Social Sciences; the teacher uses a student-centered approach with cooperative learning models and scientific methods as well as various types of cooperative learning, although the combination of the two subjects (IPA and IPS) are considered less effective. However, with various creativities and innovations created by the teacher, the learning process can still run well. The implications of this research for IPAS learning in the classroom are as an alternative for teachers in carrying out science learning to build students' understanding of IPAS comprehensively. Besides that, the results of this research are expected to be input for policymakers in deciding or providing a policy in a curriculum.